Модифікації 7-гідрокси-3-(бензотіазол-2-іл)кумарину - Шокол, Т.В.; Супрун, А.В.; Глібов, Є.К.; Москвіна, В.С.; Хиля, В.П. (Доповіді НАН України, 2021)
Проведено модифікацію 7-гідрокси-3-(бензотіазол-2-іл)кумарину, що містить диметиламінометильну та формільну групи в 8-му положенні бензопіран-2-онового циклу, корисні для подальших структурних перетворень. Амінометилюванням 7-гідрокси-3-(бензотіазол-2-іл)кумарину за класичних умов реакції Манніха з використанням надлишку формаліну отримані похідні системи дигідрооксазинокумарину. На основі 8-діалкіламінометил-7-гідрокси-3-(бензотіазол-2-іл)кумарину переамінуванням з бензиламінами синтезовані відповідні основи Манніха, в результаті взаємодії з енамінокетонами о-гідроксіаренів — похідні гомо - і зофлавону, за умов реакції Даффа — 3-(бензотіазол-2-іл)-7-гідрокси-8-формілкумарин. Останній у реакції з 4-нітрофенацилбромідом утворює похідну системи фуро[2,3-h]кумарину. Досліджено рециклізації 3-(бензотіазол-2-іл)-7-гідрокси-8-(4-оксо-4Н-3-хроменілметил)-2Н-2-хроменону під дією бінуклеофілів. This paper is devoted to 7-hydroxy-3-(benzothiazol-2-yl)coumarin modifications using the dimethylaminomethyl and formyl groups introduced in 8 position, useful for further structural transformations. Derivatives of the dihydrooxazinocoumarin system were obtained by aminomethylation of 7-hydroxy-3-(benzothiazol-2-yl) coumarin under the classical Mannich reaction conditions using an excess of formalin. Starting from 8-dialkylaminomethyl-7-hydroxy-3-(benzothiazol-2-yl)coumarin the corresponding Mannich bases were synthesized by transamination with benzylamines, homoisoflavone derivatives were obtained as a result of the interaction with o-hydroxyarene enaminoketones and 3-(benzothiazol-2-yl)-7-hydroxy-8-formylcoumarin was obtained under the Duff reaction conditions. The latter in the reaction with 4-nitrophenacyl bromide formed the furo[2,3-h]coumarin system derivative. The recyclizations of 3-(benzothiazol-2-yl)-7-hydroxy- 8-(4-oxo-4H-3-chromenylmethyl)-2H-2-chromenone under the action of binucleophiles were studied.